Bullying Intervention in Schools: A Multilevel Analysis of Teachers' Success in Handling Bullying From the Students' Perspective. (May 2019) - Wachs, Sebastian; Bilz, Ludwig; Niproschke, Saskia; Schubarth, Wilfried
To date, little has been known about teachers' success in bullying interventions. Thus, the present study analyzes how successfully teachers intervene in real bullying situations, based on an analysis of 1, 996 reports by German students aged between 12 and 15 (49.2% female) from 24 schools. Predictors of success included intervention strategy (authoritarian-punitive, supportive-individual, supportive-cooperative intervention), bullying form (physical, verbal, relational, cyber), and the student's bullying role (bully, victim, bystander) in the particular situation. Multilevel analyses showed that supportive-cooperative intervention strategies were the most successful in dealing with bullying in both the short and long term. In the long term, students evaluated teachers as being more successful in dealing with cyberbullying compared with physical bullying. Compared with students who observed bullying, students who perpetrated it were less likely to report that teachers' interventions were successful in the short term. Implications for bullying intervention, preservice teacher-training, and future research are discussed.